2007
DOI: 10.1007/s00068-007-7079-4
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Trauma Revisited*

Abstract: Pancreatic trauma is rare with an incidence between one and two percent in patients with abdominal trauma. Morbidity and mortality, however, are significant with rates approaching 40-45% in some reports. The majority of patients with injuries to the pancreas have associated trauma to other organs which are primarily responsible for the high mortality rate. The continuity of the main pancreatic duct is the most important determinant of outcome after injury to the pancreas. If there is no evidence of ductal inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
(114 reference statements)
0
17
0
Order By: Relevance
“…Subramanian and Feliciano concur with the aforementioned findings and claim that if there is no evidence of pancreatic duct disruption on fine-cut C/T or ERCP, NOM is favoured [16].…”
Section: Treatment Of American Association For the Surgery Of Trauma mentioning
confidence: 71%
See 3 more Smart Citations
“…Subramanian and Feliciano concur with the aforementioned findings and claim that if there is no evidence of pancreatic duct disruption on fine-cut C/T or ERCP, NOM is favoured [16].…”
Section: Treatment Of American Association For the Surgery Of Trauma mentioning
confidence: 71%
“…Most authors agree that a distal pancreatectomy is indicated for grade III pancreatic injuries with transection of the pancreas to the left of the mesenteric vessels [16,21]. In the case of a stable child under 10 years of age or a stable adult with an isolated pancreatic injury, splenic salvage should be considered.…”
Section: Treatment Of Grade Americal Association Of the Surgery Of Trmentioning
confidence: 97%
See 2 more Smart Citations
“…The indications for decompressive surgery, and the techniques and management of the ensuing open abdomen are challenging issues explored in this Focus on-issue that hopefully stimulates the discussion for future options and trends, and helps the readers in updating their knowledge in trauma and emergency surgery of the pancreas. I wish to express my gratitude to Dr. Subramanian [6], Dr. Feliciano [6], and Dr. De Waele [7] for their excellent contributions and thank for their support over the years.…”
Section: Focus On Emergency Surgery Of the Pancreasmentioning
confidence: 99%